2013
DOI: 10.1007/bf03405648
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life of Canadian Forces Veterans After Transition to Civilian Life

Abstract: M ilitary personnel transitioning from military service to civilian life undergo a complex, multifaceted process with variable institutional, health, psychological, work, family, and community dimensions. 1-4 For most, transition is relatively smooth; for some, transition is characterized by decreased wellbeing, including compromised physical and mental health, social problems, role disability, disadvantages in determinants of health and decreased quality of life. 5 While there is no clear consensus on how to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 20 publications
3
42
0
Order By: Relevance
“…Little can be done by military organizations to directly address the experiences of military personnel prior to their service. Nevertheless, it could be useful to develop interventions that target the various pathways through which ACEs influence mental health to mitigate their impact, particularly because many of these proposed pathways involve factors that have been linked to better mental health in military and veteran populations (Cigrang et al, 2014;Han et al, 2014;Lee, Sudom, & McCreary, 2011;Lee, Sudom, & Zamorski, 2013;Pietrzak, Johnson, Goldstein, Malley, & Southwick, 2009;Polusny et al, 2011;Solomon & Mikulincer, 1990; Thompson et al, 2013;Watkins, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Little can be done by military organizations to directly address the experiences of military personnel prior to their service. Nevertheless, it could be useful to develop interventions that target the various pathways through which ACEs influence mental health to mitigate their impact, particularly because many of these proposed pathways involve factors that have been linked to better mental health in military and veteran populations (Cigrang et al, 2014;Han et al, 2014;Lee, Sudom, & McCreary, 2011;Lee, Sudom, & Zamorski, 2013;Pietrzak, Johnson, Goldstein, Malley, & Southwick, 2009;Polusny et al, 2011;Solomon & Mikulincer, 1990; Thompson et al, 2013;Watkins, 2014).…”
mentioning
confidence: 99%
“…Broadly defined as an individual's sense of control over his or her life circumstances, mastery has been found to be inversely related with various types of childhood abuse in the civilian literature (Comijs et al, 2013), and has been found to mediate the relationship between low childhood socioeconomic status and adult health (Kan, Kawakami, & Umeda, 2015). Mastery has also been found to be associated with better health and health-related quality of life in studies of Canadian military personnel and veterans (Lee et al, 2011;Thompson et al, 2013).…”
mentioning
confidence: 99%
“…Military characteristics, VAC status and demographic characteristics were obtained through data linkage with DND and VAC administrative databases and self-report. Details of this computer-assisted telephone survey conducted by Statistics Canada and the variables contained and extracted from the DND and VAC administrative databases are reported elsewhere ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of chronic pain and associated characteristics may differ between Veterans in Canada versus the United States due to military service factors, such as role in conflict zones, and conditions after release from the military, such as access to health and social services. Recent Canadian studies suggest that chronic pain in Veterans is associated with low physical health-related quality of life ( 11 ) and suicidal ideation ( 12 ). The purpose of the present study was to explore the prevalence of chronic pain in Canadian Veterans and identify potential correlates of chronic pain.…”
mentioning
confidence: 99%
“…The question of how those who serve in the military fare after they leave service has been a topic of long‐standing interest within the United States and around the world (Pinder et al., ; Thompson et al., ; Vogt et al., ). Within the United States, there are over 19 million military veterans (US Department of Veterans Affairs, National Center for Veterans Analysis and Statistics, ) and more than 40,000 organisations devoted to promoting their health, vocational, financial, and social well‐being (Berglass & Harrell, ; Pedersen et al., ).…”
Section: Introductionmentioning
confidence: 99%